Muskuloskelettal Medicine - Jarnagin JJ; McCormack M; McInnis KC; Borg-Stein J; Tenforde AS (Dynamic Media Sales Verlag, 2023)
Plantar fasciitis is one of the most common causes of foot and heel pain in adults. Extracorporeal shockwave therapy (ESWT) and platelet-rich plasma (PRP) have each been described as effective treatments for plantar fasciitis; however, the combined use has not been adequately described. This report characterizes successful return to sport in two runners with plantar fasciitis who were treated with ESWT combined with PRP. Patient-reported outcomes were measured using the Foot and Ankle Ability Measure (FAAM). A 69-year-old female had 8 months of pain refractory to physical therapy (PT). A 73-year-old male presented with recent onset of 3 weeks of symptoms. Both runners had exam findings of plantar fasciitis and MRI confirmation. Each elected to complete ESWT along with PT using a foot core program and met functional improvements for both sport and ADL subscales of FAAM after initial ESWT treatment. However, each runner had worsening pain when attempting to run and both elected to proceed with a single leukocyte-poor PRP injection combined with ESWT. This allowed for successful return to running. Both cases highlight how combined ESWT and PRP with a foot core PT progression may be effective in managing plantar fasciitis in running athletes.Key Words: Regenerative Medicine, Running, Extracorporeal Shockwave Therapy (ESWT), Foot and Ankle Ability Measure (FAAM)